O dilema da participação local na cooperação transfronteiriça Brasil-França (1990-2015) - Carmentilla das Chagas Martins; Cavlak, Iuri (Dialogos, 2020)
From the 1980s/90s, Brazilian foreign policy adopted a more assertive agenda regarding neighboring countries in northern South America. In this context, the celebration of the Framework Agreement between Brazil and France is inserted, an institutional framework that implemented cross-border cooperation between Amapá and French Guiana. At the time, France was interested in projecting itself politically and commercially in South America. On the other hand, Brazil has also achieved success with this new agenda. However, after twenty-four years in force, cross-border cooperation does not show effectiveness regarding the results expected by the collectives on both sides of the Guyano-Amapá border. This article seeks to discuss that the lack of local participation has become a contender in the development of this cooperation, which has not resulted in a political project capable of promoting the aggregation of cultural matrices that stimulate an identity of objectives. To development the reflection, non-participant observation, interviews with residents in the city of Oiapoque were used, as well as the examination of some agreements concluded between Brazil and France and the minutes of the meetings of the Joint Cross-Border Commission-CTM. The specificities that make the Guyano-Amapá border interesting to the governments of Brazil and France are found in the temporal experiences of multiple actors, unrelated to chronologies, but rather to the length of life lived.